The molecular and structural bases for the association of complement C3 mutations with atypical hemolytic uremic syndrome. Issue 2 (August 2015) - Martínez-Barricarte, Rubén; Heurich, Meike; López-Perrote, Andrés; Tortajada, Agustin; Pinto, Sheila; López-Trascasa, Margarita; Sánchez-Corral, Pilar; Morgan, B. Paul; Llorca, Oscar; Harris, Claire L.; Rodríguez de Córdoba, Santiago
Highlights: Mutations in C3 have been associated with aHUS and other glomerulopathies. aHUS-associated C3 mutants R592W, R161W, and I1157T impair regulation by MCP, but not by FH. EM analysis provides the structural basis for the functional impairment of the R161W and I1157T mutants. Data supports aHUS-associated C3 mutations selectively affect complement regulation on surfaces. Abstract: Atypical hemolytic uremic syndrome (aHUS) associates with complement dysregulation caused by mutations and polymorphisms in complement activators and regulators. However, the reasons why some mutations in complement proteins predispose to aHUS are poorly understood. Here, we have investigated the functional consequences of three aHUS-associated mutations in C3, R592W, R161W and I1157T. First, we provide evidence that penetrance and disease severity for these mutations is modulated by inheritance of documented "risk" haplotypes as has been observed with mutations in other complement genes. Next, we show that all three mutations markedly reduce the efficiency of factor I-mediated C3b cleavage when catalyzed by membrane cofactor protein (MCP), but not when catalyzed by factor H. Biacore analysis showed that each mutant C3b bound sMCP (recombinant soluble MCP; CD46) at reduced affinity, providing a molecular basis for its reduced cofactor activity. Lastly, we show by electron microscopy structural analysis a displacement of the TED domain from the MG ring in C3b in two of the C3 mutants that explains these defects in regulation. As a whole our data suggest that aHUS-associated mutations in C3 selectively affect regulation of complement on surfaces and provide a structural framework to predict the functional consequences of the C3 genetic variants found in patients.